Patrimonio alimentario y turismo gastronómico del cantón Alausí, provincia de Chimborazo - Julissa Alejandra, Chafla Sifuentes (2021)
ABSTRACT The Food Heritage of the Alausí city is devalued, its main cause being the ignorance that the population possesses, in terms of ancestral and gastronomic knowledge. The main objective of the research is to analyze the relationship between food heritage and gastronomic tourism in the Alausí city, Chimborazo province. For this, the methodology used is documentary, descriptive and correlational, since information from bibliographic sources such as academic / scientific articles, undergraduate / graduate thesis, technical reports, gastronomic magazines, among others, was based. The design is non- experimental and transectional or transversal causal, since evaluation instruments were applied in the month of March to the population under study. From a mixed approach, a field work was carried out, in which quantitative data was collected, through the application of surveys to the owners and / or managers of the food and beverage establishments registered in the tourist registry of the Unidad de Turismo y Cultura del Gobierno Autónomo Descentralizado Municipal of Alausí city (GADMCA), in order to measure their level of knowledge regarding agricultural practices, nutritional properties, ways of conservation and food transformation. In the same way, several interviews were applied, information that helped to identify local products, cooking techniques, traditions and customs in the preparation of local dishes. Based on the results, it was identified that the population, owners and workers of the restaurants have a low-medium level of knowledge regarding the indicators of the independent variable. While, the dependent variable identified the main gastronomic activities for tourists according to their level of importance. Finally, it is concluded to carry out as a proposal communicational strategies of the food heritage of the canton, in order to preserve and maintain those inherited knowledge that still remain in the living memory of the Alauseña population. Keywords: Heritage, tourism, identity, strategies, knowledge. Reviewed by: Lcda. Diana Chávez ENGLISH PROFESSOR C.C. 065003795-5